2017
DOI: 10.1038/s41467-017-00394-x
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement determines the timing dependence of corticostriatal synaptic plasticity in vivo

Abstract: Plasticity at synapses between the cortex and striatum is considered critical for learning novel actions. However, investigations of spike-timing-dependent plasticity (STDP) at these synapses have been performed largely in brain slice preparations, without consideration of physiological reinforcement signals. This has led to conflicting findings, and hampered the ability to relate neural plasticity to behavior. Using intracellular striatal recordings in intact rats, we show here that pairing presynaptic and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 58 publications
(112 reference statements)
7
83
0
Order By: Relevance
“…In slice preparations, NMDAR, Ca 2+ /calmodulin–dependent protein kinase II (CaMKII) and D1R regulate the enlargement of the dendritic spine, a structural basis for long-term potentiation of the D1R-expressing spiny projection neurons (D1-SPNs) in the NAc (Yagishita et al, 2014). Of note, the phasic burst of dopamine potentiated the spine enlargement when dopamine followed glutamatergic inputs within 0.3 – 1 s in the D1-SPNs (Yagishita et al, 2014) and similar narrow time windows of dopamine for plasticity have been shown in other studies (Wieland et al, 2015; Fisher et al, 2017). The behavioral time window, however, can also be affected by the times for sensory and reward information processing, and by other rules for plasticity (Hebb, 1949; Cassenaer and Laurent, 2012; Fremaux and Gerstner, 2015; Brea et al, 2016).…”
Section: Introductionsupporting
confidence: 84%
“…In slice preparations, NMDAR, Ca 2+ /calmodulin–dependent protein kinase II (CaMKII) and D1R regulate the enlargement of the dendritic spine, a structural basis for long-term potentiation of the D1R-expressing spiny projection neurons (D1-SPNs) in the NAc (Yagishita et al, 2014). Of note, the phasic burst of dopamine potentiated the spine enlargement when dopamine followed glutamatergic inputs within 0.3 – 1 s in the D1-SPNs (Yagishita et al, 2014) and similar narrow time windows of dopamine for plasticity have been shown in other studies (Wieland et al, 2015; Fisher et al, 2017). The behavioral time window, however, can also be affected by the times for sensory and reward information processing, and by other rules for plasticity (Hebb, 1949; Cassenaer and Laurent, 2012; Fremaux and Gerstner, 2015; Brea et al, 2016).…”
Section: Introductionsupporting
confidence: 84%
“…However, in their protocol dopamine activity was induced during, but not after, the preand postsynaptic pairing activity, thus demonstrating critical timing requirements but not showing silent eligibility traces outlasting glutamatergic excitation. Recently, Fisher et al (2017), reported in anaesthetized rats, that a delayed sensory stimulus paired with stimulation of the substantia nigra pars compacta modulated corticostriatal spike-timing dependent plasticity in a manner consistent with an eligibility trace. However, the pairing of presynaptic and postsynaptic activity was applied at the onset of an up state, during which the barrages of afferent activity that sustain the up state continued, so that there was no silent period free of glutamatergic excitation.…”
Section: Discussionmentioning
confidence: 95%
“…Now, an existing and inactive ternary complex in AC5 regulation has consequences on how this "gate" would be opened: disinhibition from active Gα i is necessary, accompanied by stimulation from Gα olf . That is, our findings suggest that experimentally observed ACh ↓ in the striatum is likely physiologically relevant for D 1 MSNs, and both a Da ↑ and a ACh ↓ are necessary to enable synaptic potentiation (see also [46]). They can also help in interpreting the functional role of the neuromodulatory signals in the striatum.…”
Section: Relevance For Corticostriatal Synaptic Plasticitymentioning
confidence: 53%